Zebrafish as model system for the biological characterization of CK1 inhibitors - Meier, Laura; Gahr, Bernd Martin; Roth, Aileen; Gihring, Adrian; Kirschner, Stefan; Woitaske-Proske, Clemens; Baier, Joana; Peifer, Christian; Just, Steffen; Knippschild, Uwe (Frontiers in Pharmacology, 2023)
The CK1 family is involved in a variety of physiological processes by regulating different signaling pathways, including the Wnt/β-catenin, the Hedgehog and the p53 signaling pathways. Mutations or dysregulation of kinases in general and of CK1 in particular are known to promote the development of cancer, neurodegenerative diseases and inflammation. There is increasing evidence that CK1 isoform specific small molecule inhibitors have promising therapeutic potential, including CK1δ-and CK1εspecific inhibitors of Wnt production (IWP)-based small molecules with structural similarity to benzimidazole compounds. In this study, we investigated the suitability of the zebrafish model system for the evaluation of such CK1 inhibitors. To this end, the kinetic parameters of human CK1 isoforms were first compared with those of zebrafish orthologues revealing that zebrafish CK1δA and CK1δB were inhibited as effectively as human CK1δ by compounds G2-2 with IC50 values of 345 and 270 nM for CK1δA and CK1δB versus 503 nM for human CK1δ and G2-3 exhibiting IC50 values of 514 and 561 nM for zebrafish CK1δA and B, and 562 nM for human CK1δ. Furthermore, the effects of selective CK1δ inhibition on zebrafish embryonic development in vivo revealed phenotypic abnormalities indicative of down-regulation of CK1δ. Treatment of zebrafish embryos with selected inhibitors resulted in marked phenotypic changes including blood stasis, heart failure, and tail malformations. These results suggest that the zebrafish is a suitable in vivo assay model system for initial studies of the biological relevance of CK1δ inhibition.